Free Cash Flow, Financial Distress, and Earnings Management: The Moderating Role of Independent Commissioner - Rafi Anan Dzulfikar; Amrie Firmansyah (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2022)
This study examines the effect of free cash flow and financial distress on earnings management. In addition, this study also examines the role of the independent commissioner as a moderator in the relationship between the independent and dependent variables. The research data is obtained from the financial statements of transportation sub-sector companies in Indonesia listed on the Indonesia Stock Exchange (IDX) for 2018-2020. Based on the purposive sampling method, the final samples used in this study amounted to 87 observations. This study concludes that free cash flow is negatively associated with earnings management, while financial distress is positively associated with earnings management. This study also finds that independent commissioners strengthen the negative effect of free cash flow on earnings management, and independent commissioners weaken the positive effect of financial distress on earnings management. This study indicates that the Financial Services Authority (OJK) needs to carry out supervision and improvement related to the provisions on the recruitment of independent commissioners to improve corporate governance and investor protection.